2008
DOI: 10.1163/156854008783797561
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of the blue crab, Callinectes sapidus Rathbun, 1896 (Decapoda, Brachyura, Portunidae) in the eastern Adriatic (Croatian coast)

Abstract: On 15 October 2004, four specimens of the blue crab, Callinectes sapidus were caught near Ston (Pelješac peninsula, south-eastern Adriatic) in a hypersaline lagoon (salt pond) at a depth of 0.50 m. An other specimen was caught in the Neretva River estuary on 1 October 2004 at a depth of 7 m, and a second one at the same location on 6 December 2006 at a depth of 5 m. The records from this study constitute the first report of this species from the eastern Adriatic coast and confirm the spreading of C. sapidus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…In conclusion, although previous investigations have focused on C. sapidus populations in the Neretva River estuary (Onofri et al, 2008;Dulčić et al, 2010Dulčić et al, , 2011, this study is the first using stable isotope analysis to present original and quantitative information on the trophic role of the blue crab, and to cast this invasive species within the trophic structure of the benthic food web. More studies are necessary in order to provide an advanced resolution of the functional role of C. sapidus in Croatian waters and assess its potential ecological impact on coastal benthic communities.…”
Section: Discussionmentioning
confidence: 81%
“…In conclusion, although previous investigations have focused on C. sapidus populations in the Neretva River estuary (Onofri et al, 2008;Dulčić et al, 2010Dulčić et al, , 2011, this study is the first using stable isotope analysis to present original and quantitative information on the trophic role of the blue crab, and to cast this invasive species within the trophic structure of the benthic food web. More studies are necessary in order to provide an advanced resolution of the functional role of C. sapidus in Croatian waters and assess its potential ecological impact on coastal benthic communities.…”
Section: Discussionmentioning
confidence: 81%
“…The spreading of the two panopeid crabs in the Adriatic Sea in recent years (FROGLIA & SPE-RANZA, 1993;MIZZAN & ZANELLA, 1996;ONOFRI et al, 2008) has been facilitated by the development of mussel aquaculture both in lagoons and open sea, with transfer of mussels seed and half grown mussels among aquaculture plants.…”
Section: Alien Crustaceans In the Adriatic Seamentioning
confidence: 99%
“…The first record in Hellenic waters dates back to 1947-1948(Serbetis, 1959, but Nehring (2011) suggested that the species was present as early as 1935 in the Gulf of Thessaloniki. Recent records in the Adriatic-Ionian Sea refer to Croatia (Onofri et al, 2008;Dulčić et al, 2011), Italy (Florio et al, 2008), Albania (Beqiraj and Kashta, 2010) and Greece (Eleftheriou et al, 2011). The last record was based on a female specimen collected close to the mouth of the River Pamisos in SW Greece and therefore, documentation on the presence of the species is lacking for a large part of the Eastern Ionian Sea, ranging from northern Albania to southern Greece.…”
Section: Documentation On the Establishment Ofmentioning
confidence: 99%